O início da docência de professores da educação superior - Hees, Luciane Weber Baia (2016)
This study is a result of an inquietation of a higher education teacher who after many years of undergraduate teaching proposes a reflexive thinking about the initiation of the professors in higher education. The scientific production about higher education teachers has been characterized by a few and isolates studies. The formation of this professional is one of the most important elements for the quality of the higher education, therefore, we understand that it is pertinent to take a close look at the history and legislation of higher education, the required qualities that this professor must have, the professionalism and the teacher s development in the beginning of this professional career. The goal of the study was to analyze how these teaching professionals live the beginning of their teaching in a confessional university center. The thesis is that the analyses of the reality lived by the professors in the beginning of their careers is able to propose initiatives of supporting the new teacher in higher education. Theoric framework were taken from Huberman (1992) who characterizes the 5 first years of teaching as a period of surviving and discovery; Marcelo Garcia (1999), Zabalza (1994), Cunha (2012), Andre (2012), Anastasion (2014), Vaillant (2014), Roldão (2006) among others, who study the formation, insertion and professionality of teachers and support this study. It was used the qualitative approach of research, beginning of the understanding that the professors, in the beginning of their teaching need to have a support and monitoring because the first years of professional work are permeated by many challenging situations that interfere significantly in their professional status. The semi-structured interview and the documental analysis were used as a methodological procedure. Themes were established in data analyzes which follows: who is the beginner professor, challenges and difficulties in the beginning of the career, the formative necessities of the beginner professor of higher education and how the institutional environment influences the teaching. Results indicated that the beginner higher education professor is responsible for his own insertion to find the way to adapt and survive his professional reality. The field of knowledge that the professor is going to teach and the necessity to impose the authority through the profession are the main concerns identified in the beginning of teaching. One of the characteristics from the institutional environment, the beginning professors demonstrated the desire to be part of and fit to the context of the institution. The organizational environment prevails in the professor s routine and produces a feeling of belonging to the institution. The beginner professors face the academic competition and they complain about the lack of time of living that enable exchanges and dialogues. It is necessary to rethink spaces to the teaching construction for shared teaching knowledge. The results led us to some notes for the elaboration of support proposes to the beginner professional